TÜRKIYE’S INTERNATIONAL IMAGE: A MEDIA ANALYSIS IN ENGLISH, FRENCH, AND GERMAN MEDIA (2010–2025) (Isagoge - Journal of Humanities and Social Sciences, 2025)
Between 2010 and 2025, Türkiye has positioned itself as a significant actor in regional and global politics. Key events such as the Gezi Park protests, the Syrian Civil War, the July 15 coup attempt, and transformations in foreign policy strategies have been pivotal in shaping Türkiye’s international image. This study aims to examine how international media represents Türkiye’s domestic and foreign policy developments and how these representations influence global perceptions. Drawing on Joseph Nye’s concept of soft power, Türkiye’s diplomatic initiatives, cultural projects, and crisis management strategies are evaluated as critical factors in the formation of its international image. Media framing and agenda-setting theories provide a foundational analytical framework for understanding the media’s role in this process. The research analyzes news coverage from leading English-, French-, and German-language media outlets through content analysis and framing analysis to explore the dominant themes shaping Türkiye’s international image, the evolution of this image over the 2010–2025 period, and whether regional differences exist among media outlets in different geographies. The study’s primary limitations include its reliance on digital and accessible sources for data collection and potential losses of cultural/linguistic nuances during translation. Nevertheless, through a longitudinal and comparative approach, this study aims to make an original and comprehensive contribution to the literature on Türkiye’s international image.